The effect of feeding molasses or sorghum based diets on some reproductive and productive traits of Nilotic ewes - Atta M.; El Khidir O.A. (Advanced nutrition and feeding strategies to improve sheep and goat, 2007)
Forty two multiparous (PF) and 27 young (YE) Nilotic ewes were used. Each age group was subdivided into sorghum (So) and molasses (Mo) based diet groups. The two diets were iso-nitrogenous (21.7% CP) with approximately the same metabolisable energy content [12.2 (So) and 11.4 MJ/kg DM (Mo)]. Each diet group consisted of six subgroups of similar weights. The data were collected for two successive lambing seasons. The overall means of birth weight, weaning weight, pre-weaning weight gain, age and weight at lambing for the two YE diet groups were 2.3 ± 0.5 kg, 11.7 ± 2.4 kg, 104 ± 26.2 g/day, 410.6 ± 60.4 days and 29.3 ± 4.2 kg, respectively. Ewes of the PF groups had higher indices of total weight of weaned lambs/ewe than the YE groups. It is concluded that molasses can be safely fed up to 50% of the diet of Nilotic ewes with satisfactory results of growth and reproduction.
11. Seminar of the FAO-CIHEAM Sub-Network on Sheep and Goat Nutrition, 2005/09/08-10, Catania (Italy)